O Discurso Persuasivo Na Cidade: Retórica, Medicina E Arte No Górgias E Na República De Platão - Santos, Claudiano Avelino Dos [UNIFESP] (2018)
This Doctoral Thesis Begins With The Critique Of Rhetoric As Art (""""") In The Gorgias Dialogue, In Order To Demonstrate The Positive Elements Of Persuasion In Platonic Thought. Therefore, It Takes A Scene Of The Dialogue As Inspiration: Gorgias, The Rhetor, Next To Herodicus, His Brother, Who Is A Physician, Trying To Cure An Ill Man (Gorg. 456 B 1 Ff.). The Physician Has The Knowledge, But Cannot Convince The Diseased To Undergo Treatment; The Physician Has No Knowledge Of Medical Procedures, But, Using The Right Words, Persuades The Patient To Take The Medication. However, According To Socrates' Argument In Gorgias, Only Medical Practice Is An Art ("""""). Why? What Does Rhetoric Lack In Order To Be A Form Of Art In The Service Of The City? Guided By This Question, The Thesis Analyses The Role Of Art In The First Three Books Of The Republic. For This Purpose, The City (""""") Is Considered As The Place Where Human Beings Gather To Satisfy Their Needs Through Art. It Is Perceived That Art, In The Republic,